The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1989
DOI: 10.1116/1.575931
|View full text |Cite
|
Sign up to set email alerts
|

Diamond and diamondlike films: Deposition processes and properties

Abstract: Considerable interest has been aroused in the synthesis of diamond films due to their potential applications in microelectronics and optoelectronics. Although synthesis of diamond films by a variety of chemical and plasma assisted chemical as well as physical vapor deposition techniques has been reported, the practical applications of these coatings are still very few. The basic reason limiting the applications of these coatings is the inability to deposit films with smooth surface morphology and desired optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Tahara et al reported diamond-like carbon (DLC) films prepared by plasma-assisted CVD [3]. Many studies have been performed on the synthesis mechanisms of the DLCs, which are very attractive materials for hard manufacturing tools and excellent electrical insulating films [4][5][6][7][8][9]. However, the interaction between a plasma and a substrate target surface is not clear because particle-species compositions, temperatures and densities of the plasma as well as plasma behaviors near the surface cannot easily be measured even with recent advanced diagnostic methods [3].…”
Section: Introductionmentioning
confidence: 99%
“…Tahara et al reported diamond-like carbon (DLC) films prepared by plasma-assisted CVD [3]. Many studies have been performed on the synthesis mechanisms of the DLCs, which are very attractive materials for hard manufacturing tools and excellent electrical insulating films [4][5][6][7][8][9]. However, the interaction between a plasma and a substrate target surface is not clear because particle-species compositions, temperatures and densities of the plasma as well as plasma behaviors near the surface cannot easily be measured even with recent advanced diagnostic methods [3].…”
Section: Introductionmentioning
confidence: 99%
“…Diamond-like carbon (DLC) thin films have been developed for a wide range of mechanical, tribological, optical, electrical and biomedical applications due to their high hardness, chemical inertness and thermal conductivity, tunable optical and electrical properties, and good biocompatibility [1,2]. However, high electrical resistivity and residual stress of DLC films are major challenges for their electrochemical applications.…”
Section: Introductionmentioning
confidence: 99%
“…DLC containing hydrogen is called hydrogenated amorphous carbon (a-C:H) [1]. DLC has similar properties to diamond such as high hardness, high wear resistance, high transparency in the infrared range, chemical inertness, and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…DLC has similar properties to diamond such as high hardness, high wear resistance, high transparency in the infrared range, chemical inertness, and biocompatibility. Due to these properties, the interest in DLC has grown for various applications in modern industries such as protective coatings, microelectronic systems, optical coatings and biomedical applications [1][2][3].…”
Section: Introductionmentioning
confidence: 99%